Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Bill Heusinkveld, December 20, 1986 - Heusinkveld, Billet al (1986)
Iowa Christmas bird counts of regular and uncommon species found at Lake Rathbun contributed by Bill Heusinkveld, December 20, 1986. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1986-1987. Epson - sheet feed